If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -4x = 11 + -10x Combine like terms: -3x + -4x = -7x -7x = 11 + -10x Solving -7x = 11 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -7x + 10x = 11 + -10x + 10x Combine like terms: -7x + 10x = 3x 3x = 11 + -10x + 10x Combine like terms: -10x + 10x = 0 3x = 11 + 0 3x = 11 Divide each side by '3'. x = 3.666666667 Simplifying x = 3.666666667
| -5x+14x-x= | | X^2-33x-280=0 | | -7(2x+3)=-34-8x+7x | | 2(1-2x)=14 | | -1+-3= | | 1x+6=7 | | 5a+7=17 | | -2+-1= | | 3n-7=5n+9 | | 4(6x+2)-5(x-2)=6x-54+x | | -1/2+(-1/3)= | | 155+90= | | 1*2= | | 3a^2+30a+63= | | 1.2*-5= | | X-1=1+x | | 5x-8=3x+5 | | 13=29-8x | | 9/20+1/5= | | 3z=-5.85 | | 2z=2.1 | | -9-0= | | 4[-5x+7-3(x+1)]=-5x+4 | | -4x+7+6x=13 | | t=5n+5v | | -3-10= | | 2+3x+6x=2 | | ln(x)=ln(6)+ln(x-4) | | 7x+3y=-21 | | 7x-3+4x=96 | | -2x+3=-1 | | 1+4x+x=36 |